Lifelong motor development - Gabbard, Carl 1948- (Wolters Kluwer Health, 2018)
Approaching motor development as the study of change, Lifelong Motor Development , 7th Edition, offers the most up-to-date, comprehensive, research-based coverage of motor behavior across the life span available today. Rather than introducing a single theory, the book covers the most prominent theories and views that underscore our understanding of change in motor development to help students truly understand the multicausal and complex nature of motor development across the lifespan. Now in vibrant full color, the 7th Edition offers much that is new, including new content that reflects the latest research, new pedagogy, new illustrations, and an enhanced suite of resources that help students succeed and ensure easy integration into the classroom.